A human resource auditing model with the approach of functional and macro level strategies in hospitals - Somayeh Poursoltani Zarandi; Malikeh Beheshtifar; Amin Nikpour (Shahid Beheshti University of Medical Sciences, 2022)
Background: The aim of this study was presenting a human resource auditing model strategies in hospitals affiliated to social security organization. Methods: This study was conducted using a qualitative method. The statistical population of the study included audit and human resources elites in hospitals affiliated with social security in Kerman, ten of them were selected using purposeful (non-probabilistic) sampling method. During the study and survey of experts, 106 indicators for the implementation of functional and macro level strategies were identified and were placed in the form of 15 concepts. The content validity index of the questionnaire was confirmed with a value of larger than 0.79. The developed questionnaire was submitted to 10 human resources experts. Kappa coefficient index has been used to determine the reliability, Fuzzy Delphi technique and cognitive mapping method are used to analyze the data of this study. The data in the final cross-matrix questionnaire were used as input data for the Ucinet and NetDraw system to design the pattern. Results: 106 Indicators were determined under 15 categories including mental, psychological, physical and scientific skills, interaction, allocation, organization, supervision, thinking, professional, cognitive, individual, interpersonal, strategic and managerial. It was individual skills. Management skills were identified as a focal node called the ego with nodes directly connected to the alter. Conclusion: The results of the present study can be used by managers to the rules, goals and macro policies of related organizations.